2016
DOI: 10.1007/s11356-016-7705-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance and microbial community structures of hydrolysis acidification process treating azo and anthraquinone dyes in different stages

Abstract: In this study, performance of hydrolysis acidification process treating simulated dyeing wastewater containing azo and anthraquinone dyes in different stages was investigated. The decolorization ratio, COD removal ratio, BOD/COD value, and volatile fatty acids (VFAs) production were almost better in stage 1 than that in stage 2. Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectrometry (GC-MS) confirmed the biodegradation of Reactive Black 5 (RB5) and Remazol Brilliant Blue R (RBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…As illustrated in Fig. 5, the dye colour removal changed inversely to the initial dye concentration of RR4 [26]. Higher colour removal rate was obtained for the process study where the initial dye concentration of 10ppm solution relative lower initial concentration while the dye concentration was increased 10 times further.…”
Section: Effect Of Dye Concentrationmentioning
confidence: 83%
“…As illustrated in Fig. 5, the dye colour removal changed inversely to the initial dye concentration of RR4 [26]. Higher colour removal rate was obtained for the process study where the initial dye concentration of 10ppm solution relative lower initial concentration while the dye concentration was increased 10 times further.…”
Section: Effect Of Dye Concentrationmentioning
confidence: 83%
“…Whereas, high molecular weight and complex structure containing dyes have low decolorization rate (Li et al, 2019). Increased dye concentration decreases dye decolorization and/or degradation (Liu et al, 2016).…”
Section: Soluble Saltsmentioning
confidence: 99%
“…4). Liu et al (2017) found a new bacterial laccase from Klebsiella pneumoniae that could efficiently decolorize anthraquinone dyes. More enzymes with potential value for the biocatalysis of anthraquinone dyes are needed, because of their high efficiency.…”
Section: Enzymatic Anthraquinone Dye Degradation Mechanismsmentioning
confidence: 99%
“…In general, the dye decolorization rate decreases with increasing dye concentration. Liu et al (2017) reported that the decolorization rate of Remazol Brilliant Blue R reached more than 70% at low concentrations (10-30 mg/L) and then declined sharply, ultimately reaching only 15% at 200 mg/L. Printing and dyeing wastewater can have variable water quality, and the chromaticity difference can reach more than 4000 times, which requires researchers to cultivate and domesticate degradative bacteria that can adapt to a wide range of dye concentrations.…”
Section: Effect Of Dye Concentration and Structure On Bacterial Anthrmentioning
confidence: 99%